1998
DOI: 10.1002/(sici)1096-9861(19981026)400:3<417::aid-cne10>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem inputs to the ferret medial geniculate nucleus and the effect of early deafferentation on novel retinal projections to the auditory thalamus

Abstract: Following specific neonatal brain lesions in rodents and ferrets, retinal axons have been induced to innervate the medial geniculate nucleus (MGN). Previous studies have suggested that reduction of normal retinal targets along with deafferentation of the MGN are two concurrent factors required for the induction of novel retino-MGN projections. We have examined, in ferrets, the relative influence of these two factors on the extent of the novel retinal projection. We first characterized the inputs to the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Three earlier studies based on retrograde transport of horseradish peroxidase suggest similarities as well as differences between the present data and results from cats (Henkel, 1983), mustache bat (Casseday et al, 1989) and ferrets (Angelucci et al, 1998). The mustache bat is the most unique, with nearly all subcollicular MG-projecting cells located in a single nucleus, the nucleus of the central acoustic tract (Casseday et al, 1989).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Three earlier studies based on retrograde transport of horseradish peroxidase suggest similarities as well as differences between the present data and results from cats (Henkel, 1983), mustache bat (Casseday et al, 1989) and ferrets (Angelucci et al, 1998). The mustache bat is the most unique, with nearly all subcollicular MG-projecting cells located in a single nucleus, the nucleus of the central acoustic tract (Casseday et al, 1989).…”
Section: Discussionsupporting
confidence: 60%
“…Henkel (1983) and Casseday et al (1989) described projections to the MG from cells in or near the ventral nucleus of the lateral lemniscus (VLL). Angelucci et al (1998) subsequently described subcollicular projections to the MG that originated from the dorsal tegmental regions and areas near the VLL, as described in earlier studies, and also from additional cells in medial and lateral superior olivary nuclei. Finally, more recent work has revealed a direct projection to the MG from the cochlear nucleus (Malmierca et al, 2002; Anderson et al, 2006; Schofield et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Thus, the increase in c‐Fos and Arc/Arg3.1 immunoreactivity in the VCA shown herein suggests a homeostatic response after thalamic glutamatergic overactivation of the VCA, most likely after intermodal reorganization. A crossmodal invasion from LGN (lateral geniculate nucleus) to MGN (medial geniculate nucleus) has been shown by tract tracing experiments after early extensive removal of visual inputs, providing an anatomical substrate for understanding polimodal conversion of thalamo cortical inputs (Angelucci, Clascá, & Sur, ). Accordingly, recent studies have indicated an effective induction of thalamic plasticity in adult cortices (Cooke & Bear, ; Heynen & Bear, ; Montey & Quinlan, ; Oberlaender, Ramirez, & Bruno, ; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1). Under these conditions, retinal axons project to the contralateral medial geniculate nucleus (MGN) and to a lesser extent to the ipsilateral MGN (11,(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%